STRATEGI KOMUNIKASI PEMASARAN DIGITAL INSTAGRAM @KANOPI_MURAH UNTUK MENINGKATKAN JASA PEMASANGAN - Tata Santika; Amalliah; Cindya Yunita Pratiwi (Program Studi Komunikasi dan Penyiaran Islam, 2026)
CV Mitra Kanopi is a construction company that utilizes Instagram as a digital marketing communication platform to reach consumers, build trust, and increase service demand. This study aims to analyze the digital marketing communication strategy implemented through the Instagram account @kanopi_murah and identify supporting and inhibiting factors. The research method used is qualitative, with data collected through interviews, observations, and documentation. Data analysis employs the interactive model by Miles and Huberman, which includes three main stages: data reduction, data display, and conclusion drawing. The theoretical framework refers to Kotler and Keller’s digital marketing concept, specifically Integrated Marketing Communication (IMC). The results show that the digital communication strategy has been quite effective through five key elements: advertising, personal selling, sales promotion, public relations, and direct marketing. The success of the strategy is supported by attractive visual content, fast and responsive service, and optimal use of Instagram’s features. Challenges faced include limited human resources to consistently manage the account and difficulties in keeping up with rapidly changing social media trends. Future research is recommended to explore the effectiveness of digital communication strategies across multiple platforms